Bhagavadgītā and Mānavadharmaśāstra on War and Migration - Lehtonen, Tommi (Society for Indian Philosophy and Religion, 2026)
This article examines the perspectives on war and migration presented in the Bhagavadgītā and the Law Code of Manu, two ancient Hindu texts. The Bhagavadgītā promotes warrior ethics which emphasise self-mastery and duty without attachment, framing the justification for war as both a moral and spiritual probe. The Law Code of Manu primarily regulates everyday life while also addressing aspects of religious devotion and the social consequences thereof. The Manu code of war emphasises ethical conduct, the protection of innocents, and restraint, illustrating a robust humanitarian tradition in ancient Indian thought. The Bhagavadgītā promotes a balance between universal compassion and practical responsibility, it acknowledges the necessity for responsible governance and a vision of humanity unified by the shared spiritual essence of all beings. The Law Code of Manu does not specifically address immigration, although it delineates rules for individuals travelling abroad, particularly regarding their familial duties and responsibilities.
Keywords: war; migration; warrior ethics; self-mastery; duty; fi=Viestintätieteet|en=Communication Studies|